Malay-language stemmer - Sankupellay, Mangalam; Valliappan, Subbu (Sunway University College, 2006)
Stemming is the removal of affixes (prefixes and suffixes) in a word in order to generate its root word. The objectives of this research were to build a software stemmer that can stem any given Malay word, and to develop a standard stemming algorithm for the Malay language. The Malay language was chosen because a complete stemmer for this language is unavailable. Stemmers have a wide variety of applications, such as in information retrieval and machine translation. It is expected that when this system is fully developed, it will benefit users and customers tremendously.